MANAGEMENT OF COVID-19 IN PRISON: VARIOUS COUNTRIES AND COMPARATION WITH INDONESIAN CASE STUDY - Risma Wardiani; Adik Wibowo (Journals of Ners Community, 2022)
On December 2019, there was a discovery of a new strain of coronavirus originated from Wuhan, China. The Virus spreads easily inter human caused by droplets. Corona Virus enters Indonesia since March 2020. Correctional health is the essence of public health. The COVID-19 pandemic poses a great threat to the world and has shown that preventing the disease escalation in prisons integrates the Novel Corona Virus clash in society in general. Jail are epicenters for COVID-19 transmission, including to the community and in Indonesia has a lot of overcrowded of prisoners. Overcrowding until 102% and it occurred almost all over Indonesia. of this literature review is to analyze each country's management for Covid-19 in Prison, and how the Prison in Indonesia response in particular. the search for articles and journals will be conducted via web browsing, using the database such as Science direct, PubMed, and Google Scholar. The applied keywords will be Covid-19 management in Prison and Jail. As many as 9 related articles are match with the inclusion and exclusion criteria. Prisons and detention area are intensively vulnerable to infectious diseases because they are highly crowded places where social distancing is difficult. Several countries applied the management of Covid-19 in Prison. Through this principle, every prisoner and detainee must be treated humanely and according to dignity, based on human rights aspect. Many factors make the results different in each country, such as the speed of the enactment of policies, lack of vigor in medical protocol enforcement to the prisoners and staffs, or the lack of risk awareness by the people themselves. The study shows the management Covid-19 in Prison can be traced back to the speed of the policy enactment, the force to enforce the medical protocol, limiting access to a prison area, and finally a massive screening Covid-19 for prisoners and staffs.